The SDIDTK–My Plate Model to Improve Maternal Nutrition Literacy and Child Growth - Neherta, Meri; Hermalinda; Novrianda, Dwi; Mansur, Arif Rohman; Sari, Ira Mulya; Rahmadhani, Dian; Rahmanelly, Suci; Yantje, Oktavvia Fittrianna; Rilda, Yuli (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2026)
Malnutrition and delayed child growth remain critical challenges in Indonesia, primarily driven by low maternal nutritional literacy and inadequate early stimulation. Addressing these issues is vital to reduce the high stunting prevalence and improve child development outcomes. This study aimed to evaluate the SDIDTK-Isi Piringku (Stimulation, Detection, and Early Intervention - My Plate) model using a quasi-experimental pre-post test design without control. The intervention was conducted on 30 mothers of children under two years old and Posyandu cadres at Bungus Health Center, Padang City. The results demonstrated a significant enhancement in maternal knowledge and attitudes regarding child growth, leading to a 45% increase in nutritional literacy. Furthermore, the intervention successfully strengthened family-community collaboration. In conclusion, the SDIDTK-Isi Piringku community-based model is proven effective in empowering mothers. This model serves as a strategic prototype for local policies to prevent stunting and supports the achievement of Sustainable Development Goals (SDGs) 2, 3, and 4.